Pengaruh Profitabilitas, Struktur Modal, dan Likuiditas terhadap Nilai Perusahaan Manufaktur Makanan dan Minuman - Nur Azda; Simon Hendrik Leasa; Hansen Hein Rumtutuly (TIN: Terapan Informatika Nusantara, 2026)
This study aims to examine the effect of profitability, capital structure, and liquidity on firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2024 period. In this study, Return on Assets (ROA) is used as a proxy for profitability, Debt to Equity Ratio (DER) represents capital structure, Current Ratio (CR) is employed to measure liquidity, while Price to Book Value (PBV) serves as an indicator of firm value. A quantitative approach was adopted, employing multiple linear regression analysis to examine the relationships among the variables. The study utilized secondary data obtained from the annual financial statements of food and beverage manufacturing companies listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling technique, resulting in a total of 80 observations. The findings reveal that profitability has no significant effect on firm value (sig. = 0.307). In contrast, capital structure has a positive and significant effect on firm value (sig. = 0.001). Liquidity, however, does not have a significant effect on firm value (sig. = 0.225). The coefficient of determination of 15.1% indicates that the independent variables included in the model explain a portion of the variation in firm value. These findings highlight the importance of effective capital structure management in enhancing firm value and enhancing investor interest. Nevertheless, this study is limited to three independent variables and focuses exclusively on food and beverage manufacturing companies during the 2021-2024 period. Therefore, future research is recommended to expand the scope of the study by incorporating additional variables, such as dividend policy, firm size, firm growth, and macroeconomic factors, as well as extending the research object and observation period to obtain more comprehensive empirical evidence.